Temporal and spatial variations of soil moisture – Precipitation feedback in East China during the East Asian summer monsoon period: A sensitivity study - Zhong, Shi; Yang, Tao; Qian, Yun; Zhu, Jian; Wu, Futing (Atmospheric research, 2018)
Numerical simulations using a state-of-the-art model WRF are conducted to investigate the impact of initial soil moisture disturbance (early May) on subsequent summer precipitation during the East Asian summer monsoon period. The control experiment with the realistic soil moisture condition can well reproduce the spatial distribution of accumulated precipitation, as well as the temporal evolution of rainfall belt in East China. Major findings concerning the soil moisture impact on summer precipitation are the following. (1) The influence of initial soil-moisture on subsequent precipitation is regionally dependent, i.e., the dry soil moisture condition leads to less precipitation over both South China and Central China, and much more precipitation in coastal regions in East China. (2) The impact on non-convective precipitation is twice greater than that on convective rainfall, indicating a dominant role of initial soil moisture in total precipitation via the modification of the large-scale precipitation processes. (3) The soil moisture effect on daily precipitation highly varies with different rainfall events during the monsoonal season, suggesting a great uncertainty of soil moisture–precipitation feedback process on synoptic scale. Therefore, it is of great meaning to examine the feedback between soil moisture and precipitation on climatic scale. (4) The drier soil moisture condition reduces the rainfall frequency from light to heavy precipitation in Central China, but increases the occurrence of nearly all categories of rainfall rates in the coastal region in East China. For South China region, however, the drier soil moisture condition leads to more occurrence of light to middle precipitation categories (2–10 mm/d), and less frequency to heavy rainfall (>10 mm/d). •The influence of initial soil moisture on precipitation is regionally dependent.•The impact on non-convective precipitation is twice greater than convective rainfall.•The impact on daily precipitation varies with different rainfall events during EASM.